Trade and Employment: Evidence from Latin America and the Caribbean - Carmen Pagés-Serra; Gustavo Márquez (Inter-American Development Bank, Office of the Chief Economist, 1998)
This paper examines the impact of the recent wave of trade liberalization and economic reform on employment. Four alternative measures of openness and four measures of the real exchange rate are used to measure the impact of trade reforms on manufacturing and economy-wide employment. Across a wide range of specifications, trade reforms have had a negative, albeit small, effect on employment growth. This effect has been reinforced by real exchange rate appreciation.
Keywords: 330; Handelsliberalisierung; Erwerbstätigkeit; Lateinamerika; Karibische Staaten